Plane sets allowing bilipschitz extensions - Alestalo, P.; Trotsenko, D. A. (MATHEMATICA SCANDINAVICA, 2009)
We give a geometric characterization for a plane set AR^2 to have the following linear bilipschitz extension property: For 0ε δ, every (1 + ε)-bilipschitz map fA→ R^2 has a (1 + Cε)-bilipschitz extension to the whole plane R^2.